Micro-mechanical model for ultra-high strength and ultra-high ductility cementitious composites (UHS-UHDCC). (18th January 2021) - Lei, Dong-Yi; Guo, Li-Ping; Li, Ying; Liu, Jia-Ping; Chen, Bo; Li, Dong-Xu; Li, Shao-Chun; Mechtcherine, Viktor
Highlights: There is no the debonding displacement and the sharp stress drop before slipping for PE fiber. The slip-hardening parameter ( β ) increases with the increasing of PE fiber inclination. The inclination increases, the maximum pullout load decreases, and the slipping displacement decreases for PE fiber. More fiber pullout energy is consumed during the slipping, so the UHS-UHDCC exhibits an ultra-high ductility. Abstract: This study finds that the slip-hardening parameter ( β ) increases with the increasing of PE (Polyethylene) fiber inclination for UHS-UHDCC (ultra-high strength and ultra-high ductility cementitious composites), the slip-hardening increasing coefficient ( ω ) is introduced to correct the β of ECC model. Therefore, the single PE fiber pullout micro-mechanical model is proposed, and this study defines the debonding behavior of PE fiber as the 'physical debonding'. The pullout load–displacement curve of the single PE fiber and the single crack stress-opening curve verify the correctness of proposed micro-mechanical model for UHS-UHDCC. The first-crack stress ( σ fc, 5.78 MPa) and the fiber bridging complementary energy ( J b ', 352.1 J/m 2 ) satisfy the strength and the energy criteria, this ensures the realization of the tensile strain-hardening behavior. This study provides a theory basis for realizing the multi-cracking strain hardening behavior of UHS-UHDCC.